A kind of high temperature resistant powder coating and preparation method thereof
By using a filler system with modified graphene oxide and monodispersed hollow nanoparticles in powder coatings, the problem of the decline in high temperature resistance under high temperature conditions is solved, and the uniform performance and stability of the coating film at high temperatures is achieved.
Patent Information
- Application Number
- CN202510048347.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional powder coatings are difficult to maintain the overall high temperature resistance of the coating film under high temperature conditions, and it is easy to rapidly decline the coating's high temperature resistance due to local failure.
Using a filler system including modified graphene oxide, modified graphene oxide consists of a graphene oxide matrix and monodispersed hollow nanoparticles embedded between its layers. It is prepared by ultrasonic dispersion and low-temperature calcination, combining inorganic nanofillers with specific particle size distribution and spherical morphology to improve the thermal conductivity and density of the coating.
It effectively improves the thermal conductivity and density of the coating, avoids coating failure caused by excessive heat concentration, and maintains the overall uniformity and stability of the coating film under high temperature conditions.
Smart Images

Figure BDA0005239212810000081 
Figure BDA0005239212810000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coatings, and more specifically, relates to a high temperature resistant powder coating and a preparation method thereof. Background Art
[0002] In high temperature environments, the oxidation corrosion rate of metal materials accelerates, seriously affecting the mechanical properties and service life of industrial equipment. The application of high temperature resistant coatings can greatly improve the anti-corrosion effect of the substrate in high temperature environments, extend the service life and maintenance cycle of equipment, and save maintenance costs. It has broad application prospects in the fields of petrochemicals, pipelines, metallurgy, electrical appliances, aerospace, etc. High temperature resistant coatings are divided into two categories: organic and inorganic according to their composition. The film-forming material of organic high temperature resistant coatings is mainly silicone resin, and the high temperature resistant coatings with inorganic adhesives as the main film-forming material are inorganic high temperature resistant coatings.
[0003] For high temperature resistant powder coatings, the resin as the base material should have a very high thermal decomposition temperature, and a special modified resin should be selected; the filler is the skeleton of the heat resistant coating, which can greatly improve many properties of the coating. Different fillers play different roles in the coating, such as talcum powder, hollow micropowder, quartz powder, mica powder, etc., which have high heat resistance, chemical resistance, radiation resistance, non-flammability, etc. The use of resin or filler alone cannot achieve the purpose of high temperature resistance, only the combination of the two can work. In addition, a variety of fillers can be used to obtain coatings with good comprehensive performance. The flaky structure of mica powder can improve the density of the coating, prevent water penetration, and provide excellent heat resistance, water resistance, acid and alkali resistance and good electrical insulation; the fine particle structure of talcum powder can improve the hardness, weather resistance and corrosion resistance of the coating; the coarse particle structure of hollow micropowder can improve the hardness, heat resistance and wear resistance of the coating. Their microstructures are different, and the combination of the three can obtain ideal crack resistance. The more filler is added, the better the heat resistance, weather resistance, corrosion resistance and other properties of the coating will be, but the powder coating rate will deteriorate and the appearance of the coating will also deteriorate accordingly. Summary of the invention
[0004] The technical problem to be solved by the present invention is that it is difficult for traditional powder coatings to effectively maintain the overall high temperature resistance of the coating under high temperature conditions during actual use, and the high temperature resistance of the coating is easily reduced rapidly due to local failure. Based on the above difficulties, the present invention provides a high temperature resistant powder coating and a preparation method thereof.
[0005] The purpose of the present invention is to provide a high temperature resistant powder coating.
[0006] Another object of the present invention is to provide a method for preparing a high temperature resistant powder coating.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A high temperature resistant powder coating comprising a polyester resin, a curing agent and a filler;
[0009] The filler includes modified graphene oxide;
[0010] The modified graphene oxide comprises a graphene oxide matrix and monodisperse hollow nanoparticles embedded between layers of the graphene oxide matrix;
[0011] The monodisperse hollow nanoparticles are selected from any one of monodisperse hollow nanoalumina, monodisperse hollow nanosilicon dioxide, monodisperse hollow nanomagnesia, monodisperse hollow nanozinc oxide, and monodisperse hollow nanotitanium dioxide;
[0012] The D50 of the monodisperse hollow nanoparticles is 3-5 nm; the particle size distribution range of the monodisperse hollow nanoparticles is 1-10 nm;
[0013] The D50 of the graphene oxide matrix is 10-20 μm.
[0014] Beneficial technical effects of the above technical solution:
[0015] For high temperature resistant powder coatings, the aforementioned technical problems of high temperature resistant coatings formed by curing after the coating is used are improved by adding a filler system mainly composed of modified graphene oxide;
[0016] Specifically, first of all, the reason why graphene oxide is selected as one of the filler components is that graphene oxide itself has excellent thermal conductivity on the plane formed by the x and y directions. As a filler in the polyester resin system, it is easy to accumulate with each other to form a continuous heat conduction path, so that heat can be quickly and evenly transferred on the surface of the high-temperature resistant coating formed by the curing of the coating, avoiding coating failure caused by excessive heat concentration in the layout;
[0017] Secondly, the inventors found that although relying solely on rapid heat transfer on a plane constructed in the x and y directions can alleviate the failure caused by heat concentration to a certain extent, in the z direction, due to the gaps between graphene oxide layers, its thermal conductivity is low, and it is difficult to achieve heat balance. This problem can be solved by embedding inorganic nanofillers between its layers; but at the same time, due to the introduction of inorganic nanofillers, the density of graphene oxide will increase. In the actual curing film forming process, it is difficult to evenly distribute the fillers in the thickness direction. The use of hollow inorganic fillers can solve this problem to a certain extent; in addition, the inventors found that when inorganic nanofillers are embedded between graphene oxide layers, if the particle size distribution range is too wide, large particles will cause the interlayer spacing to be excessively expanded when embedded between layers, and small particles will be difficult to effectively "bridge" the heat transfer path between layers, thereby weakening the role of inorganic nanofillers. The use of monodisperse inorganic nanofillers with a narrow particle size distribution range effectively solves this problem.
[0018] Furthermore, the curing agent is selected from any one of β-hydroxyalkylamide, triglycidyl trimellitate, and HDI-hexamethylene diisocyanate.
[0019] Furthermore, the surface of the monodisperse hollow nanoparticles is coated with a coupling agent; the coupling agent is selected from any one of a silane coupling agent, a phthalate coupling agent, and an aluminate coupling agent.
[0020] Furthermore, the sphericity of the monodisperse hollow nanoparticles is 9.0-9.2.
[0021] Beneficial technical effects of the above technical solution:
[0022] The inventors further discovered that, since the orientation of monodisperse hollow nanoparticles is often random when they are embedded or stacked between graphene oxide layers, different particles, although having the same or similar particle sizes and relatively uniform particle size distribution, if the sphericity of the particles is low, especially below 9.0, when the particles are stacked in the long axis direction and the short axis direction, a large difference in the interlayer spacing between the graphene oxide layers will be generated, thereby weakening the effect of "bridging" the heat transfer path between the layers; and particles with a sphericity greater than 9.2 will place higher requirements on the manufacture and screening of the particles, resulting in a significant increase in cost.
[0023] Furthermore, the amount of the filler is 1.2-1.5 times the mass of the polyester resin.
[0024] Furthermore, the filler further comprises boehmite accounting for 8-10% of the mass of the modified graphene oxide; and the D50 of the boehmite is 0.3-0.6 μm.
[0025] Beneficial technical effects of the above technical solution:
[0026] Since the preparation of the coating is accompanied by a crushing process, some inorganic nanofillers may be separated from the graphene oxide matrix during the crushing process and become free. Their surface energy is high and they are easy to agglomerate, resulting in local uneven high-temperature resistance in the coating system. By adding a certain amount of boehmite, whose particle size is smaller than that of the graphene oxide matrix, it can be used to adsorb and fix the detached inorganic nanofillers, and is expected to synergistically fill the gaps formed during the mutual stacking of modified graphene oxide, thereby improving the density of the coating film.
[0027] A method for preparing a high temperature resistant powder coating, the specific preparation steps comprising:
[0028] Preparation of modified graphene oxide:
[0029] After mixing graphene oxide and water, ultrasonic dispersion is continued at an ultrasonic frequency of more than 200 kHz for more than 1 hour, and then monodisperse hollow nanoparticles are added, and ultrasonic dispersion is continued for more than 10 minutes, and then the filter cake is collected by suction filtration, and the filter cake is low-temperature calcined at a temperature of 180-200° C. in an inert atmosphere to constant weight, cooled, and discharged to obtain modified graphene oxide;
[0030] During the processing, a certain temperature is used for calcination, so that the residual water between the graphene oxide layers during the preparation process can be fully volatilized, avoiding the residual water during product processing or use, which will cause the high temperature resistance of the coating to decrease due to the volatilization of water;
[0031] Among them, the reason why there is residual moisture during the processing is mainly because the distance between graphene oxide layers is widened, which makes it easy for moisture to enter. Secondly, because inorganic fillers are embedded between the layers, they have a good affinity with water and are also prone to water retention.
[0032] Preparation of high temperature resistant powder coating:
[0033] The polyester resin, the curing agent and the filler including the modified graphene oxide are mixed, melt-extruded, cooled and tableted, crushed and sieved to obtain the high temperature resistant powder coating.
[0034] Furthermore, the preparation of the modified graphene oxide also includes:
[0035] The monodisperse hollow nanoparticles are dispersed in an ethanol solution, a coupling agent is added, and after heating and stirring for reaction, the monodisperse hollow nanoparticles are filtered, washed and dried to obtain pretreated monodisperse hollow nanoparticles.
[0036] After mixing graphene oxide and water, ultrasonic dispersion is continuously performed at an ultrasonic frequency of more than 200 kHz for more than 1 hour, and then pretreated monodisperse hollow nanoparticles are added. After ultrasonic dispersion is continued for more than 10 minutes, the filter cake is collected by suction filtration, and the filter cake is low-temperature calcined at a temperature of 180-200° C. in an inert atmosphere to constant weight, cooled, and discharged to obtain modified graphene oxide.
[0037] Furthermore, the preparation of the high temperature resistant powder coating also includes:
[0038] The polyester resin, the curing agent, and the fillers including the modified graphene oxide and boehmite are mixed, melt-extruded, cooled and tableted, crushed, and sieved to obtain the high temperature resistant powder coating. DETAILED DESCRIPTION
[0039] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0040] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0041] In the monodisperse hollow nanoparticles mentioned below, the specific meaning of hollow is that bubbles are introduced by using emulsifiers or the like during the preparation process, so that the inside of the particles is in a hollow state, as distinguished from a completely solid state.
[0042] Example 1
[0043] Preparation of modified graphene oxide:
[0044] The monodisperse hollow nanoparticles are dispersed in a 10% ethanol solution, a coupling agent is added, and after heating and stirring for reaction, the pretreated monodisperse hollow nanoparticles are filtered, washed and dried; wherein the amount of the ethanol solution is 15 times the mass of the monodisperse hollow nanoparticles, and the amount of the coupling agent is 10% of the mass of the monodisperse hollow nanoparticles;
[0045] Wherein, the monodisperse hollow nanoparticles are selected from monodisperse hollow nanoalumina;
[0046] The D50 of the monodisperse hollow nanoparticles is 3 nm; the particle size distribution range of the monodisperse hollow nanoparticles is 1-10 nm;
[0047] The sphericity of the monodisperse hollow nanoparticles is 9.0;
[0048] The coupling agent is selected from silane coupling agents;
[0049] After mixing graphene oxide and water, ultrasonic dispersion is continued at an ultrasonic frequency of more than 200 kHz for 1.2 hours, and then pre-treated monodisperse hollow nanoparticles are added, and ultrasonic dispersion is continued for 12 minutes, and then filtered to collect the filter cake, and the filter cake is low-temperature calcined at 180° C. in an inert atmosphere to constant weight, cooled, and discharged to obtain modified graphene oxide;
[0050] The amount of monodisperse hollow nanoparticles used was 0.1 times the mass of graphene oxide;
[0051] The modified graphene oxide and boehmite with a mass percentage of 8% of the modified graphene oxide are uniformly mixed to serve as a filler; wherein the D50 of the boehmite is 0.3 μm;
[0052] Preparation of high temperature resistant powder coating:
[0053] According to weight, take 500 parts of polyester resin, 30 parts of curing agent, 4 parts of defoaming agent, 6 parts of leveling agent, and filler 1.2 times the weight of polyester resin;
[0054] Wherein, the curing agent is selected from β-hydroxyalkylamide;
[0055] The materials were stirred and mixed at a stirring speed of 400 r / min for 5 min to obtain a premix;
[0056] The premix was melt extruded through a twin-screw extruder, and the temperature of the extruder was set as follows: 70°C in zone I, 90°C in zone II, and a screw speed of 800 r / min;
[0057] After cooling, crushing and passing through a 160-mesh sieve, high temperature resistant powder coating is obtained.
[0058] Example 2
[0059] Preparation of modified graphene oxide:
[0060] The monodisperse hollow nanoparticles are dispersed in an ethanol solution with a mass fraction of 10%, and a coupling agent is added, and after heating and stirring for reaction, the pretreated monodisperse hollow nanoparticles are filtered, washed and dried; wherein the amount of the ethanol solution is 18 times the mass of the monodisperse hollow nanoparticles, and the amount of the coupling agent is 10% of the mass of the monodisperse hollow nanoparticles;
[0061] Wherein, the monodisperse hollow nanoparticles are selected from monodisperse hollow nanosilica;
[0062] The D50 of the monodisperse hollow nanoparticles is 4 nm; the particle size distribution range of the monodisperse hollow nanoparticles is 1-10 nm;
[0063] The sphericity of the monodisperse hollow nanoparticles is 9.1;
[0064] The coupling agent is selected from phthalate coupling agents;
[0065] After mixing graphene oxide and water, ultrasonic dispersion is continued at an ultrasonic frequency of 210 kHz for 1.3 hours, and then the pretreated monodisperse hollow nanoparticles are added, and ultrasonic dispersion is continued for 15 minutes, and then the filter cake is collected by suction filtration, and the filter cake is low-temperature calcined at a temperature of 190° C. in an inert atmosphere to constant weight, cooled, and discharged to obtain modified graphene oxide;
[0066] The amount of monodisperse hollow nanoparticles used was 0.1 times the mass of graphene oxide;
[0067] The modified graphene oxide and boehmite with a mass percentage of 9% of the modified graphene oxide are uniformly mixed to serve as a filler; wherein the D50 of the boehmite is 0.5 μm;
[0068] Preparation of high temperature resistant powder coating:
[0069] According to weight, take 520 parts of polyester resin, 31 parts of curing agent, 5 parts of defoaming agent, 7 parts of leveling agent, and filler 1.3 times the weight of polyester resin;
[0070] Wherein, the curing agent is selected from triglycidyl trimellitate;
[0071] The materials were stirred and mixed at a stirring speed of 400 r / min for 5 min to obtain a premix;
[0072] The premix was melt extruded through a twin-screw extruder, and the temperature of the extruder was set as follows: 75°C in zone I, 95°C in zone II, and a screw speed of 900 r / min;
[0073] After cooling, crushing and passing through a 160-mesh sieve, high temperature resistant powder coating is obtained.
[0074] Example 3
[0075] Preparation of modified graphene oxide:
[0076] The monodisperse hollow nanoparticles are dispersed in an ethanol solution with a mass fraction of 10%, and a coupling agent is added. After heating and stirring for reaction, the pretreated monodisperse hollow nanoparticles are filtered, washed and dried. The amount of the ethanol solution is 20 times the mass of the monodisperse hollow nanoparticles, and the amount of the coupling agent is 10% of the mass of the monodisperse hollow nanoparticles.
[0077] Wherein, the monodisperse hollow nanoparticles are selected from monodisperse hollow nano titanium dioxide;
[0078] The D50 of the monodisperse hollow nanoparticles is 5 nm; the particle size distribution range of the monodisperse hollow nanoparticles is 1-10 nm;
[0079] The sphericity of the monodisperse hollow nanoparticles is 9.2;
[0080] The coupling agent is selected from phthalate coupling agents;
[0081] After mixing graphene oxide and water, ultrasonic dispersion is continued at 250kHz ultrasonic frequency for 2h, and then pre-treated monodisperse hollow nanoparticles are added, and ultrasonic dispersion is continued for 20min, and then the filter cake is collected by suction filtration, and the filter cake is low-temperature calcined at 200°C in an inert atmosphere to constant weight, cooled, and discharged to obtain modified graphene oxide;
[0082] The amount of monodisperse hollow nanoparticles used was 0.1 times the mass of graphene oxide;
[0083] The modified graphene oxide and boehmite with a mass percentage of 10% of the modified graphene oxide are uniformly mixed to serve as a filler; wherein the D50 of the boehmite is 0.6 μm;
[0084] Preparation of high temperature resistant powder coating:
[0085] According to weight, take 550 parts of polyester resin, 32 parts of curing agent, 6 parts of defoaming agent, 8 parts of leveling agent, and filler 1.5 times the weight of polyester resin;
[0086] Wherein, the curing agent is selected from HDI-hexamethylene diisocyanate;
[0087] The materials were stirred and mixed at a stirring speed of 400 r / min for 5 min to obtain a premix;
[0088] The premix was melt extruded through a twin-screw extruder, and the temperature of the extruder was set as follows: 80°C in zone I, 100°C in zone II, and a screw speed of 1000 r / min;
[0089] After cooling, crushing and passing through a 160-mesh sieve, high temperature resistant powder coating is obtained.
[0090] Example 4
[0091] The difference between this embodiment and embodiment 1 is that boehmite is not added, and other conditions remain unchanged.
[0092] Example 5
[0093] The present embodiment differs from the embodiment 1 in that an equal mass of alumina of the same specification is used to replace boehmite, and the other conditions remain unchanged.
[0094] Example 6
[0095] The difference between this embodiment and embodiment 1 is that the sphericity of the monodisperse hollow nanoparticles is 8.8, and the other conditions remain unchanged.
[0096] Comparative Example 1
[0097] Compared with Example 1, the difference between this comparative example and Example 1 is that the preparation of modified graphene oxide is different, specifically:
[0098] The monodisperse hollow nanoparticles are dispersed in a 10% ethanol solution, a coupling agent is added, and after heating and stirring for reaction, the pretreated monodisperse hollow nanoparticles are filtered, washed and dried; wherein the amount of the ethanol solution is 15 times the mass of the monodisperse hollow nanoparticles, and the amount of the coupling agent is 10% of the mass of the monodisperse hollow nanoparticles;
[0099] Wherein, the monodisperse hollow nanoparticles are selected from monodisperse hollow nanoalumina;
[0100] The D50 of the monodisperse hollow nanoparticles is 3 nm; the particle size distribution range of the monodisperse hollow nanoparticles is 1-10 nm;
[0101] The sphericity of the monodisperse hollow nanoparticles is 9.0;
[0102] The coupling agent is selected from silane coupling agents;
[0103] After mixing graphene oxide and pretreated monodisperse hollow nanoparticles, the mixture was stirred with a stirrer for 10 minutes to obtain modified graphene oxide;
[0104] The amount of monodisperse hollow nanoparticles used was 0.1 times the mass of graphene oxide;
[0105] The rest of the conditions remain unchanged.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 1 is that no monodisperse hollow nanoparticles are added, and other conditions remain unchanged.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 1 is that monodisperse solid nanoparticles of equal mass are used to replace monodisperse hollow nanoparticles, and other conditions remain unchanged.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 1 is that the particle size distribution range of the monodisperse hollow nanoparticles is 0.1-30 nm, and the other conditions remain unchanged.
[0112] The performance tests were performed on the products obtained in the above embodiments and comparative examples. The specific test methods and test results are as follows:
[0113] The product obtained in the embodiment or comparative example was sprayed by a spray gun, the spray gun voltage was 60 kV, the atomization pressure was 40000 Pa, the powder discharge pressure was 160000 Pa, the substrate was a 0.6 mm thick cold-rolled steel plate (pre-treated by sandblasting and degreasing), and the curing conditions were 240° C. for 30 min;
[0114] The coated cold-rolled steel sheet was placed at 400°C for 12 hours, and the coating surface was observed for local cracking, bubbling or discoloration. The relevant results are recorded in Table 1.
[0115] Table 1: Product performance test results
[0116]
[0117]
[0118] It can be seen from the test results in Table 1 that the product obtained by the present invention can make the overall performance of the coating film uniform, and after long-term high-temperature treatment, the overall properties can be kept stable.
[0119] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high temperature resistant powder coating, characterized in that: including polyester resin, curing agent and filler; The filler includes modified graphene oxide; The modified graphene oxide comprises a graphene oxide matrix and monodisperse hollow nanoparticles embedded between layers of the graphene oxide matrix; The monodisperse hollow nanoparticles are selected from any one of monodisperse hollow nanoalumina, monodisperse hollow nanosilicon dioxide, monodisperse hollow nanomagnesia, monodisperse hollow nanozinc oxide, and monodisperse hollow nanotitanium dioxide; The D50 of the monodisperse hollow nanoparticles is 3-5 nm; the particle size distribution range of the monodisperse hollow nanoparticles is 1-10 nm; The D50 of the graphene oxide matrix is 10-20 μm.
2. A high temperature resistant powder coating according to claim 1, characterized in that: The curing agent is selected from any one of β-hydroxyalkylamide, triglycidyl trimellitate, and HDI-hexamethylene diisocyanate.
3. A high temperature resistant powder coating according to claim 1, characterized in that: The surface of the monodisperse hollow nanoparticles is coated with a coupling agent; the coupling agent is selected from any one of a silane coupling agent, a phthalate coupling agent, and an aluminate coupling agent.
4. A high temperature resistant powder coating according to claim 1, characterized in that: The sphericity of the monodisperse hollow nanoparticles is 9.0-9.
2.
5. The high temperature resistant powder coating according to claim 1, characterized in that: The amount of the filler used is 1.2-1.5 times the mass of the polyester resin.
6. A high temperature resistant powder coating according to claim 5, characterized in that: The filler also includes boehmite accounting for 8-10% of the mass of the modified graphene oxide; and the D50 of the boehmite is 0.3-0.6 μm.
7. A method for preparing a high temperature resistant powder coating according to any one of claims 1 to 6, characterized in that: The specific preparation steps include: Preparation of modified graphene oxide: After mixing graphene oxide and water, ultrasonic dispersion is continued at an ultrasonic frequency of more than 200 kHz for more than 1 hour, and then monodisperse hollow nanoparticles are added, and ultrasonic dispersion is continued for more than 10 minutes, and then the filter cake is collected by suction filtration, and the filter cake is low-temperature calcined at a temperature of 180-200° C. in an inert atmosphere to constant weight, cooled, and discharged to obtain modified graphene oxide; Preparation of high temperature resistant powder coating: The polyester resin, the curing agent and the filler including the modified graphene oxide are mixed, melt-extruded, cooled and tableted, crushed and sieved to obtain the high temperature resistant powder coating.
8. The method for preparing a high temperature resistant powder coating according to claim 7, characterized in that: The preparation of the modified graphene oxide also includes: The monodisperse hollow nanoparticles are dispersed in an ethanol solution, a coupling agent is added, and after heating and stirring for reaction, the monodisperse hollow nanoparticles are filtered, washed and dried to obtain pretreated monodisperse hollow nanoparticles. After mixing graphene oxide and water, ultrasonic dispersion is continuously performed at an ultrasonic frequency of more than 200 kHz for more than 1 hour, and then pretreated monodisperse hollow nanoparticles are added. After ultrasonic dispersion is continued for more than 10 minutes, the filter cake is collected by suction filtration, and the filter cake is low-temperature calcined at a temperature of 180-200° C. in an inert atmosphere to constant weight, cooled, and discharged to obtain modified graphene oxide.
9. The method for preparing a high temperature resistant powder coating according to claim 7, characterized in that: The preparation of the high temperature resistant powder coating also includes: The polyester resin, the curing agent, and the fillers including the modified graphene oxide and boehmite are mixed, melt-extruded, cooled and tableted, crushed, and sieved to obtain the high temperature resistant powder coating.
Citation Information
Patent Citations
Preparation method of nanometer boehmite composite oxidized graphene antiwear lubricant
CN105154170A
Graphene nano composite material and preparation method thereof
CN107245224A
Graphene material for hot-compress material and preparation method for graphene material
CN112057747A
Weather-resistant building waterproof coating and preparation method thereof
CN112480813A
High-performance graphene film and preparation method thereof
CN114957897A
Cited By
High-temperature-resistant anticorrosive paint for boiler and preparation method thereof
CN120310378A
Super anti-corrosion powder coating for marine facilities and preparation method of super anti-corrosion powder coating
CN122080725A